Golf Event Planning Analysis: A Case study of Fella Golf Club Bandung 2019 - Oktaviani, Desy; Sutisna, Deden; Eka Sumadhinata, Yelli; Riantani, Suskim (International Journal of Psychosocial Rehabilitation, 2020)
This research analyzes the planning of a golf match event organized by Fella Golf Club Bandung. In this case, analyzing the planning includes planning, budgets, objectives, supervision, and responsibility in the event of the events organized by Fella Golf Club Bandung. The research methods used are descriptive research methods with a qualitative approach, data obtained from interviews, and direct observation. The results derived from this research show that the event events by Fella Golf have good planning and have already been calculated with the maturity of the activities, so there is a problem in the implementation that is not in accordance with what is expected.